Damage accumulation in plasma‐sprayed zirconia under cyclic loading. Issue 9 (31st May 2022) - Lal, Devi; Ramanadham, Vyshnavi; Kumar, Praveen; Sampath, Sanjay; Jayaram, Vikram
Abstract: The stiffness and hysteretic response due to mechanical and thermo‐mechanical cycling have been studied in plasma‐sprayed yttria‐stabilized zirconia (YSZ). Mechanical cycling of free‐standing cantilevers of YSZ shows that the progressive decrease in stiffness is accompanied by monotonic increase in hysteretic energy dissipation per cycle and a permanent ratcheting displacement of ∼20 nm/cycle. Below a critical stress, it varies from coating to coating, ratcheting accompanied by a slow decrease in stiffness does not lead to failure even after ∼1000 cycles. In contrast, at higher stresses, the rates of ratcheting and decrease in stiffness increase rapidly, leading to the nucleation of macrocracks that lead to fracture failure. Prior thermal cycling of coatings on Inconel substrate up to 700°C, which induced an estimated cyclic thermal stress of ∼35 MPa, led to a pronounced reduction in stiffness and mechanical cycling life. During bending, damage accumulates in the tension side of the cantilever and the volume going through the compression cycle remains relatively undamaged. Abstract : Plasma‐sprayed thermal barrier coating contains hierarchical array of intra‐splat and inter‐splat cracks, which are oriented normal and parallel to the spray direction, respectively. Experimental and numerical simulations of their response to thermal stresses by cyclic mechanical loading of cantilevers show that degradation can be monitored through gradual stiffness reduction and ratcheting that arise from the accumulation of damage through inter‐splat sliding. Finite element analysis coupled to a cementitious model of damage shows that above a certain critical stress with increase in cycling number, vertically oriented microcracks link through weakly bonded horizontal inter‐splat boundaries to form flaws that lead to brittle failure.